2006
DOI: 10.1111/j.1365-2656.2006.01092.x
|View full text |Cite
|
Sign up to set email alerts
|

Behaviourally mediated indirect effects: interference competition increases predation mortality in foraging redshanks

Abstract: Summary1. The effect of competition for a limiting resource on the population dynamics of competitors is usually assumed to operate directly through starvation, yet may also affect survival indirectly through behaviourally mediated effects that affect risk of predation. Thus, competition can affect more than two trophic levels, and we aim here to provide an example of this. 2. We show that the foraging success of redshanks Tringa totanus (L.) foraging on active prey was highest in the front of flocks, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 59 publications
0
41
0
Order By: Relevance
“…In an earlier study of sandpipers foraging on Corophium, step rate decreased with prey density in a limited sample of three plots, but sandpiper density was not measured (Wilson and Vogel 1997). A similar finding was documented in redshanks (Tringa totanus), but food density could not be measured independently of the birds' behavior (Minderman et al 2006). In another shorebird, step rate was also reduced in enriched food patches (Santos et al 2009).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In an earlier study of sandpipers foraging on Corophium, step rate decreased with prey density in a limited sample of three plots, but sandpiper density was not measured (Wilson and Vogel 1997). A similar finding was documented in redshanks (Tringa totanus), but food density could not be measured independently of the birds' behavior (Minderman et al 2006). In another shorebird, step rate was also reduced in enriched food patches (Santos et al 2009).…”
Section: Discussionmentioning
confidence: 74%
“…During fall staging, sandpipers gather in large groups foraging predominantly for a burrowing prey, Corophium volutator (Hamilton et al 2003;Hicklin and Smith 1984;Peer et al 1986). While density of this amphipod is high on the mudflats where sandpipers forage, Corophium retreats to its burrow following close encounters with birds (Selman and Goss-Custard 1988), as is the case in other burrowing invertebrate species (Minderman et al 2006). The presence of many sandpipers is thus expected to decrease food availability for those companions immediately behind.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, there are many factors that are likely to affect the rate of prey capture success in relation to the prey that is encountered. These include the effects of prey patch density on prey capture success (Draulans, 1987;Darby et al, 2012), the effects of light level on the foraging success of visual predators (Ropert-Coudert et al, 2006), the presence of competition from other predators (Minderman et al, 2006) and the effects of individual experience (Daunt et al, 2007). For these reasons, rates of prey capture cannot be inferred from prey encounter, and methods that focus on prey encounters or capture attempts alone could significantly over-estimate the prey consumed by foraging animals.…”
Section: Prey Captures and Foraging Strategymentioning
confidence: 99%
“…We predicted that during periods of higher food density, shorebirds (all species as well as Long-toed Stints) should be more abundant based on previous studies that showed that shorebirds track resources through time (Schneider and Harrington 1981), are heavier (Verkuil et al 2006), and have higher foraging (defined here as feeding attempts) rates (Goss-Custard 1977b;Goss-Custard et al 1984). As actual foraging success is often difficult to measure (Beauchamp 2012), we also looked at step rates, which we predicted to be inversely correlated with increasing prey density (i.e., more foraging attempts per distance traveled; Goss-Custard and Durell 1987; Wilson and Vogel 1997;Minderman et al 2006;Santos et al 2006). We expected aggressive interactions between birds to be more common when bird density was high and food density was low as birds should then be more likely to compete for patchy resources (Groves 1978;Goss-Custard et al 1984).…”
mentioning
confidence: 99%